2010
DOI: 10.1073/pnas.1017346108
|View full text |Cite
|
Sign up to set email alerts
|

miR-29 and miR-30 regulate B-Myb expression during cellular senescence

Abstract: Cellular senescence is a form of irreversible growth arrest and a major tumor suppressor mechanism. We show here that the miR-29 and miR-30 microRNA families are up-regulated during induced and replicative senescence and that up-regulation requires activation of the Rb pathway. Expression of a reporter construct containing the 3′UTR of the B-Myb oncogene is repressed during senescence, and repression is blocked by mutations in conserved miR-29 and miR-30 binding sites in the B-Myb 3′UTR. In proliferating cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
160
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(172 citation statements)
references
References 33 publications
11
160
1
Order By: Relevance
“…Furthermore, overexpression of miR-29 increased cell-cycle reentry in quiescent cells, whereas overexpression of let-7 and miR-125 delayed cell-cycle reentry (35). Modulation of miR-29 can also influence senescence, an irreversible growth-arrested state, by affecting B-myb expression (36). We also showed that during quiescence some miRNAs up-regulate the translation of their target mRNAs (37).…”
Section: Significancementioning
confidence: 66%
“…Furthermore, overexpression of miR-29 increased cell-cycle reentry in quiescent cells, whereas overexpression of let-7 and miR-125 delayed cell-cycle reentry (35). Modulation of miR-29 can also influence senescence, an irreversible growth-arrested state, by affecting B-myb expression (36). We also showed that during quiescence some miRNAs up-regulate the translation of their target mRNAs (37).…”
Section: Significancementioning
confidence: 66%
“…1b). miR-29 and miR-30 are implicated in senescence 27 and the DNA damage response, 28 indicating that CR regulates such essential processes through the miRNA response. miR-203 has been suggested to be an important tumor suppressor 29 and has been shown to affect the invasive potential of prostate cancer cell lines.…”
Section: Methodsmentioning
confidence: 99%
“…The plethora of reports argue that microRNAs are master regulator of cancer biology, and deregulated expression of microRNAs affects all hallmarks of cancer [32] (Figure 2): (1) sustaining proliferative signaling (miR-21, let-7) [33,34]; (2) evading growth suppressors (miR-221 and miR-222) [35]; (3) resisting cell death (miR-34a, miR15a/16-1) [36,37]; (4) enabling replicative immortality (miR-29, miR-19b) [38,39]; (5) inducing angiogenesis (miR-210, miR-17-92 cluster) [40,41]; (6) activating invasion and metastasis (miR-10b, miR-224) [25,42]; (7) reprogramming energy metabolism (miR-23, miR-103) [43,44]; (8) evading immune destruction (miR-34a, miR-124a) [45,46].…”
Section: Micrornas and Human Cancermentioning
confidence: 99%